Dampak Kebijakan Akreditasi Perguruan Tinggi Terhadap Daya Saing (Competitiveness) Perguruan Tinggi Swasta Di Kabupaten Kebumen - Hendrawan Prasetyo (P4M STIE Putra Bangsa, 2014)
Accreditation policies established by the government was not fully implemented by the private universities in Kebumen. Of the five existing private universities, only two private universities that have implemented policies such accreditation STIE Putra Bangsa and STIKES Muhammadiyah Gombong. While the other three universities namely AMIK PGRI Kebumen, STTM Kebumen, and Dharma Patria Polytechnic Kebumen, accreditation policy does not apply. Accreditation policy will encourage the efforts of private universities in improving the quality and competitiveness. Some private universities are implementing quality policy efforts and make improvements. However, several other private universities have not been applied so that the accreditation policies competitiveness indicators include the number of students, academic faculty qualifications, facilities and infrastructure, and cooperation with external parties can not be optimally carried out by universities that have not implemented the policy of accreditation. The purpose of this study was to determine how the universities accreditation policy impact on the competitiveness of private universities in Kebumen. This type of research is qualitative research, retrieval of data sources using the technique of